Detection of faulted phase type in distribution systems based on one end voltage measurement - Alanzi E.A.; Younis M.A.; Ariffin A.M. (2023)
Distribution power systems exposed to various unexpected failures due to many random causes. These failures are mostly happened as a result of phase faults in power system and will affect negatively the availability and reliability of the power system. Accurate detection of these faults will help in restoration of power in a timely manner and not to cause any severe damage to the power system equipment. This paper investigates the problem of accurate detection of faulted phase types occurred in the distribution system. The features of the voltage waveforms recorded from one end measurement of the distribution system during the fault occurrence are used in the proposed technique. Clarke's transformation criterion used to identify if the fault is line-to-ground (grounded fault) or phase-to-phase (ungrounded fault). Then the fault types are classified by the high performance comparison method of the voltage signals using phase angle shift prior and during the fault occurrence. Different types of faults namely, single-phase to ground, double-phase to ground, phase-phase and balanced three-phase faults that are occurred at different locations with different fault resistances and inception angles are tested and analyzed. Results from simulation of faults on a model of 33 kV distribution system typical networks presented. © 2013 Elsevier Ltd. All rights reserved.